Mortality and morbidity of very low birth weight and extremely low birth weight babies in neonatal period - Tripathy, Saroj Kumar; Chatterjee, Kripasindhu; Behera, Narendra (International Journal of Contemporary Pediatrics, 2019)
Background: Preterm birth is one of the major clinical problems in neonatology as it is commonly associated with perinatal mortality, serious neonatal morbidity and in some cases, it leads to childhood disability. The objective of this study was to find out the outcomes of VLBW and ELBW babies in the form of mortality and morbidity in neonatal period. Methods: A cross sectional study was conducted in SNCU, MKCG Medical College, Berhampur, Odisha between 2011 to 2013. All babies with birth weight less than 1500gm, admitted between days 1 to day 7 of life were enrolled in the study. Babies were broadly divided in to two groups i.e.VLBW group (weight 1000-1499gm) and ELBW group (weight<1000gm). Details of antenatal history, sociodemographic profile and birth history including significant events were noted. Outcome measures included were death, cured and with sequelae. Results: Total number of babies enrolled in this study were two hundred twelve (n=212) and following observations were made. Mortality of ELBW babies was 61.11% and that of VLBW babies was 26.41%. Death rate in babies with weight range 500-749gm, 750-999gm, 1000-1249gm and 125-1499gm was 87.50%, 53.57%, 30.76% and 20.97% respectively. It was found that morbidities such as RDS, HIE, shock and hypoglycemia are significantly higher in ELBW babies as compared to VLBW babies. Conclusions: Extremely low birth weight babies have shown high mortality and morbidity compared to very low birth weight babies and its related death multiply when associated with complications like hyaline membrane disease, hypoxic ischemic encephalopathy, and sepsis.